2017
DOI: 10.17305/bjbms.2017.2255
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive analysis of patients with neuromyelitis optica spectrum disorder (NMOSD) combined with chronic hepatitis B (CHB) infection and seropositive for anti-aquaporin-4 antibody

Abstract: Previous research indicated the association between hepatitis B virus (HBV) infection/vaccination and the onset of demyelinating diseases. However, most of these studies were single case reports, and comprehensive data are still scarce. Here we present a comprehensive analysis of 10 patients with neuromyelitis optica spectrum disorder (NMOSD) combined with chronic hepatitis B (CHB) infection and seropositive for anti-aquaporin-4 antibody (AQP4-Ab). Demographic, clinical, laboratory, neuroimaging, outcome, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(13 citation statements)
references
References 38 publications
(38 reference statements)
1
12
0
Order By: Relevance
“…Therefore, the diagnosis of HBV-associated NMOSD was confirmed after exclusion of other infectious factors. Liu et al [ 5 ] speculated that the molecular simulation and immune cross-reaction between HBsAg and myelin antigen of the CNS may potentially explain the primary pathophysiologic mechanisms underlying NMOSD with HBV infection. Molecular simulation of T cell infective factors has been suggested as a potential mechanism of demyelination of the CNS after HBV vaccination.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, the diagnosis of HBV-associated NMOSD was confirmed after exclusion of other infectious factors. Liu et al [ 5 ] speculated that the molecular simulation and immune cross-reaction between HBsAg and myelin antigen of the CNS may potentially explain the primary pathophysiologic mechanisms underlying NMOSD with HBV infection. Molecular simulation of T cell infective factors has been suggested as a potential mechanism of demyelination of the CNS after HBV vaccination.…”
Section: Discussionmentioning
confidence: 99%
“…In both treatments, the patient's visual acuity improved after a few days; furthermore, in the second treatment, after 5 days of treatment with antiviral drugs, a rapid recovery of the liver function and gradual reduction of symptoms of systemic discomfort were observed. Liu et al [ 5 ] retrospectively analyzed 10 patients with NMOSD with CHB infection who were seropositive for AQP4-Ab; they found an increased risk of liver damage in these patients after high-dose glucocorticoid therapy. Therefore, they suggested that patients with NMOSD should be aware of the possibility of HBV infection once liver damage occurs, which would necessitate adjustments to treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…( Mormile, 2015 May ) Despite one study of 10 patients with chronic HBV and seropositive NMOSD hypothesizing a cross-reactivity between HBsAg and myelin proteins, we believe there is currently insufficient evidence to suggest that chronic HBV increases the risk for developing a demyelinating disorder. ( Liu et al, 2018 Feb 20 ) COVID-19 is far more likely to be an immunological trigger to developing autoimmune neurological disorders.…”
Section: Discussionmentioning
confidence: 99%
“…The combined results of the following searches were pooled for this table: unlimited search, search limited to H. pylori (taxid: 210), search limited to Mycobacterium tuberculosis typus humanus (taxid: 1773), and search limited to RNA viruses (taxid: 2559587). The limited searches were done due to possible associations of NMOSD with infections by H.pylori[56], M. tuberculosis[57][58][59][60], and Hepatitis viruses (RNA viruses][61][62][63]. The top Blast Hits on 100 subject sequences were analyzed.…”
mentioning
confidence: 99%